USE OF MOSSES FOR THE SURVEY OF HEAVY METAL DEPOSITION IN AMBIENT AIR OF THE KATHMANDU VALLEY APPLYING ACTIVE MONITORING TECHNIQUE - Shakya, Kumudini; Chettri, Mukesh K.; Sawidis, Thomas (Ecoprint: An International Journal of Ecology, 2014)
To understand the level of heavy metals (Cd, Co, Cr, Cu, Pb, Mn, Ni and Zn) in the ambient air of the Kathmandu valley, active monitoring technique using mosses was performed. Common mosses like Taxiphyllum giraldii (C. Muell.) Fleisch., Thuidium sparsifolium (Mitt.) Jaeg., and the leafy liverwort Ptychanthus striatus (Lehm. & Linderb.) Nees. collected from Phulchowki (a clean natural area) were transplanted at 25 different sites of the valley and were exposed for 3 months. These sites were broadly divided into 3 categories on the basis of vehicular traffic: inside Ring Road (high traffic), along Ring Road (high to moderate traffic) and outside the Ring Road (moderate to lax traffic). Three sites - Shivapuri (North-east), Raniban (North-west) and Phulchowki (South-east) were considered as control sites. Contamination Factor (CF) value obtained from the heavy metal concentration in exposed mosses indicated high contaminated sites mostly along and inside the ring road (except Zn which was found to be higher outside the ring road). On the basis of the average concentrations of the elements in the transplanted mosses, a general picture of air quality of the studied area has been ascertained. From this study, it can be made certain that ambient air of the Kathmandu valley is severely contaminated with Pb, Cr and Zn and relatively low with Co, Cu, Mn and Ni. DOI: http://dx.doi.org/10.3126/eco.v19i0.9850 Ecoprint An International Journal of Ecology Vol. 19, 2012 Page: 17-29 Uploaded date: 2/14/2014